Pronunciation instruction in Vietnamese tertiary EFL classes: Teacher cognitions and classroom practices - Đỗ Minh Luân (Trường Đại học Trà Vinh, 2023)
The overall aim of this study is to look into EFL teachers’ cognitions and classroom practices regarding pronunciation instruction in tertiary EFL educational institutions in the Mekong Delta, Vietnam.